Community-Based Education Program on Knowledge and Self-Efficacy of Type 2 Diabetes Mellitus’ Patients in Bandung - Citra Windani Mambang Sari; Ahmad Yamin; Mochmad Budi Santoso (Indonesian Contemporary Nursing Journal, 2017)
Introduction. Type 2 Diabetes Mellitus was a chronic disease have complicated. Amount of patient Type 2 Diabetes Mellitus (DM) was increased. Knowledge and self-efficacy is mainly important for self-care behavior. The purpose of this study was aimed to examine knowledge, and self-efficacy among patients with Type 2 DM in Bandung, Indonesia. Methods. The research was a quasi-experimental with pre and posttest control group. Sixty two type 2 DM were recruited from 8 working area Primary Health Centers in Bandung who have diagnosed DM, using purposive sampling technique. Knowledge questionnaire from Michigan Diabetes Research and Training Center’s Brief Diabetes Knowledge Test, Self-efficacy were measured by the developed Stanford Patients Education Research Center. Both of questionnaires comprised five dimensions: nutrition, sport and activity, drugs and glucose monitoring. Patients of in intervention group received 2 weeks Diabetes Mellitus education program be given healthcare workers. Techniques used in this program consisted of community-based education, goal setting, follow-up and face-to-face interview. Data were analyzed by independent t-test. Results. There are significantly different of knowledge and self-efficacy after community-based education program in intervention (M = 9.26, SD = 2.8 ; M = 53.26, SD = 10.50) and control group (M = 7.39, SD = 2.4; M = 36.74, SD = 4.49).  This study revealed that community-based education program significantly improved self-efficacy (p=0.000) but not improved for knowledge (p=0.180). Conclusion. These findings indicated that Knowledge and Self-efficacy of type 2 Diabetes Mellitus patients in Bandung required improvement. Therefore, further study regarding the effective in improving knowledge and self-efficacy type 2 Diabetes Mellitus is extremely needed.